# Difference between revisions of "User talk:Meljel"

(Created page with "\begin{align*} ax^2 + bx + c &= 0\\ a(x^2 + \frac bax + \frac ca) &= 0\\ a({(x + \frac {b}{2a})}^2 - \frac{b^2}{4a^2} + \frac ca) &= 0\\ {(x + \frac {b}{2a})}^2 - \frac{b^2}{4...") |
|||

Line 12: | Line 12: | ||

x &= \frac{- b \pm \sqrt{b^2 - 4ac}}{2a}\\ | x &= \frac{- b \pm \sqrt{b^2 - 4ac}}{2a}\\ | ||

\end{align*} | \end{align*} | ||

+ | {{delete|What is the point of this page?}} |

## Revision as of 16:22, 9 January 2016

\begin{align*} ax^2 + bx + c &= 0\\ a(x^2 + \frac bax + \frac ca) &= 0\\ a({(x + \frac {b}{2a})}^2 - \frac{b^2}{4a^2} + \frac ca) &= 0\\ {(x + \frac {b}{2a})}^2 - \frac{b^2}{4a^2} + \frac ca &= 0\\ {(x + \frac {b}{2a})}^2 &= \frac{b^2}{4a^2} - \frac ca\\ {(x + \frac {b}{2a})}^2 &= \frac{b^2}{4a^2} - \frac {4ac}{4a^2}\\ {(x + \frac {b}{2a})}^2 &= \frac{b^2 - 4ac}{4a^2}\\ x + \frac {b}{2a} &= \pm\sqrt{\frac{b^2 - 4ac}{4a^2}}\\ x + \frac {b}{2a} &= \pm\frac{\sqrt{b^2 - 4ac}}{2a}\\ x &= - \frac {b}{2a} \pm\frac{\sqrt{b^2 - 4ac}}{2a}\\ x &= \frac{- b \pm \sqrt{b^2 - 4ac}}{2a}\\ \end{align*}

This article has been proposed for deletion. The reason given is: What is the point of this page?.
Sysops: Before deleting this article, please check the article discussion pages and history. |